The role of diabetes in cardiomyopathies of different etiologies: characteristics and 1-year follow-up results of the EVITA-HF registry - Meindl, Christine; Hochadel, Matthias; Frankenstein, Lutz; Bruder, Oliver Helge Willy; Pauschinger, Matthias; Hambrecht, Rainer; Scheidt, Wolfgang von; Pfister, Otmar; Hartmann, Andreas; Maier, Lars S.; Senges, Jochen; Unsoeld, Bernhard (PLOS ONE, 2020)
Background Type 2 diabetes is a major risk factor for cardiovascular diseases, e.g. coronary artery disease (CAD). But it has also been shown that diabetes can cause heart failure independently of ischemic heart disease (IHD) by causing diabetic cardiomyopathy. In contrast to diabetes and IHD, limited data exist regarding patients with diabetes and dilated cardiomyopathy (DCM). Methods EVIdence based TreAtment in Heart Failure (EVITA-HF) comprises web-based case report data on demography, diagnostic measures, adverse events and 1-year follow-up of patients hospitalized for chronic heart failure and an ejection fraction <= 40%. In the present study we focused on the results of patients with diabetes and heart failure. Results Between February 2009 and November 2015, 4101 patients with chronic heart failure were included in 16 tertiary care centers in Germany. The mortality in patients with diabetes and DCM (n = 323) was more than double (15.2%) than that of DCM patients without diabetes (6.5%, p<0.001, n = 885). In contrast the mortality rate of patients withIHDwas not influenced by the presence of diabetes (17.6% in patients withIHDand diabetes n = 945, vs. 14.7% in patients withIHDand no diabetes, n = 1236, p = 0.061). The results also remained stable after performing a multivariable analysis (unadjusted p-value for interaction = 0.002, adjusted p = 0.046). Conclusion The influence of diabetes on the mortality rate is only significant in patients with DCM not in patients with CAD. Therefore, the underlying mechanisms of this effect should be studied in greater detail to improve patient care and outcome.
Gesehen am 10.05.2021